Relationship of Organizational Intelligence (OI) and Personal Creativity in Public Organizations ( A Case Study) - Yaghoubi, Nour Mohammad; Tamini, Bahman Kord; Moloudi, Jamshid (Prabandhan: Indian Journal of Management, 2011)
The study was planned to ascertain the relationship between personal creativity and organizational intelligence. In present research, the sample size consists of 156 employees (55 women and 101 men) that were selected at random from Social Security Organization of Tabriz in Iran. Albrecht Organizational Intelligence and Randcepp Creativity questionnaires were applied to collect the data. Pearson correlation coefficient, Stepwise regression and t- test were used to analyze the data. The results illustrated that there is positive significant correlation between the mean scores of creativity and organizational intelligence dimensions, namely shared fate, appetite for change, alignment and congruence, knowledge development, performance pressure and total scores of organizational intelligence (p<0.01). But results did not show significant correlation between the mean scores of creativity, strategic vision and heart. The results of stepwise regression showed that predictor variables significantly (organizational intelligence and heart) have determined 55.3% of the variance of creativity together. But other variables did not predict the creativity. The results of t test showed that there is significant difference between women and men on strategic vision i.e. men significantly had higher mean scores than women, but there was not any significant difference between two groups of gender on other variables. The results of present study reveal that we should pay specific attention to percept and improve organizational intelligence, new subject, and creativity.